The Temporal Logic of Actions - Lamport, Leslie (Microsoft, 1994)
This paper introduces TLA, which I now believe is the best general formalism for describing and reasoning about concurrent systems. The new idea in TLA is that one can use actions–formulas with primed and unprimed variables–in temporal formulas. An action describes a state-transition relation. For example, the action x'=x+1 means approximately the same thing as the programming-language statement x := x+1. However, the action is much simpler because it talks only about x and says nothing about another variable y, while the assignment statement may (or may not) assert that y doesn't change. TLA allows you to write specifications essentially the same way advocated in [82]. However, the specification becomes a single mathematical formula. This opens up a whole new realm of possibilities. Among other things, it provides an elegant way to formalize and systematize all the reasoning used in concurrent system verification. The moral of TLA is: if you're not writing a program, don't use a programming language. Programming languages are complicated and have many ugly properties because a program is input to a compiler that must generate reasonably efficient code. If you're describing an algorithm, not writing an actual program, you shouldn't burden yourselves with those complications and ugly properties. The toy concurrent programming languages with which computer scientists have traditionally described algorithms are not as bad as real programming languages, but they are still uglier and more complicated than they need to be. Such a toy program is no closer to a real C or Java program than is a TLA formula. And the TLA formula is a lot easier to deal with mathematically than is a toy program. (Everything I say about programming languages applies just as well to hardware description languages. However, hardware designers are generally more sensible than to try to use low-level hardware languages for higher-level system descriptions.) Had I only realized this 20 years ago! The first major step in getting beyond traditional programming languages to describe concurrent algorithms was Misra and Chandy's Unity. Unity simply eliminated the control state, so you just had a single global state that you reasoned about with a single invariant. You can structure the invariant any way you want; you're not restricted by the particular programming constructs with which the algorithm is described. The next step was TLA, which eliminated the programming language and allowed you to write your algorithm directly in mathematics. This provides a much more powerful and flexible way of describing the next-state relation. An amusing footnote to this paper is that, after reading an earlier draft, Simon Lam claimed that he deserved credit for the idea of describing actions as formulas with primed and unprimed variables. A similar notation for writing postconditions dates from the 70s, but that's not the same as actually specifying the action in this way. I had credited Rick Hehner's 1984 CACM article, but I figured there were probably earlier instances. After a modest amount of investigation, I found one earlier published use–in [50].
ACM Transactions on Programming Languages and Systems 16